The Effect of Video-Assisted Brain-Based Learning Model on Mathematical Critical Thinking and Mathematical Problem Solving Skills - Saputra, Wanda; Andriani, Siska; Dewi, Novian Riskiana (AlphaMath : Journal of Mathematics Education, 2024)
This study aims to determine the effect of the video-assisted Brain-Based Learning (BBL) learning model on mathematical critical thinking ability and mathematical problem-solving. This research is a quantitative research type of quasi-experimental design. The population in this study were all students in class VIII of SMPN 1 Tanjung Bintang for the 2023/2024 academic year. The sampling technique used cluster random sampling, namely three classes: class VIII B as experimental class 1 using the BBL learning model assisted by learning videos, class VIII A as experimental class 2 using the BBL learning model, and class VIII D as the control class using direct instruction learning model. The instruments used have previously been tested for validity, difficulty level, distinguishing power, and reliability. The data collection technique used was an essay test to measure mathematical critical thinking and problem-solving abilities. The data analysis techniques used are the normality test and the homogeneity test. Hypothesis testing uses the MANOVA test. Based on the results of hypothesis testing that has been carried out, it can be concluded that the BBL learning model assisted by video learning influences students’ mathematical critical thinking and mathematical problem-solving abilities. Students’ mathematical critical thinking and mathematical problem-solving skills are better using the BBL learning model assisted by learning videos than the BBL learning model and direct instruction learning model. This can be seen from calculations using MANOVA to obtain a significance level of 0.000 and value Î± test criteria = 0.05, which means p-value < Î± so that H_0AB is rejected and H_1AB is accepted.